2003
DOI: 10.1121/1.4780837
|View full text |Cite
|
Sign up to set email alerts
|

Affricate gemination in the English of Polish speakers: A study in second language variability

Abstract: This study investigates the nature of the acoustic variation in sequences of identical affricates produced by Polish learners of English. In both English and Polish sequences of identical affricates occur across word boundaries, but only in Polish do such sequences also occur root internally and across morpheme boundaries. In Polish sequences of identical affricates are manifested variably both by rearticulation of both affricates and by articulation of a single affricate but with lengthened duration of either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To our knowledge, there is only one study investigating gemination in the English spoken by Poles. Thurgood (2003) had the Polish learners perform two tasks to analyze the production of English affricate geminates across the word boundary: repetition of sentences and responding to multiple choice questions. The results revealed that a gemination strategy was correlated with the proficiency level.…”
Section: The Phonetic Features Of (Polish) Geminatesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is only one study investigating gemination in the English spoken by Poles. Thurgood (2003) had the Polish learners perform two tasks to analyze the production of English affricate geminates across the word boundary: repetition of sentences and responding to multiple choice questions. The results revealed that a gemination strategy was correlated with the proficiency level.…”
Section: The Phonetic Features Of (Polish) Geminatesmentioning
confidence: 99%
“…Contrary to the predictions, more advanced learners produced more Polish-like singly articulated affricates than intermediate learners. It was taken by Thurgood (2003) to suggest that intermediate speakers had paid more attention to the phonetics of the English cues and thus produced more rearticulated affricates.…”
Section: The Phonetic Features Of (Polish) Geminatesmentioning
confidence: 99%